Total molecular photoionization cross-sections by algebraic diagrammatic construction-Stieltjes-Lanczos method: Benchmark calculations - Ruberti, Marco; Yun, R.; Gokhberg, Kirill; Kopelke, Sören; Cederbaum, Lorenz S.; Tarantelli, F.; Averbukh, V. (The journal of chemical physics, 2013)
In [K. Gokhberg, V. Vysotskiy, L. S. Cederbaum, L. Storchi, F. Tarantelli, and V. Averbukh, J. Chem. Phys. 130, 064104 (2009)] we introduced a new - ℒ - 2 - L2 - ab initio method for the calculation of total molecular photoionization cross-sections. The method is based on the ab initio description of discretized photoionized molecular states within the many-electron Green's function approach, known as algebraic diagrammatic construction (ADC), and on the application of Stieltjes-Chebyshev moment theory to Lanczos pseudospectra of the ADC electronic Hamiltonian. Here we establish the accuracy of the new technique by comparing the ADC-Lanczos-Stieltjes cross-sections in the valence ionization region to the experimental ones for a series of eight molecules of first row elements: HF, NH3, H2O, CO2, H2CO, CH4, C2H2, and C2H4. We find that the use of the second-order ADC technique [ADC(2)] that includes double electronic excitations leads to a substantial systematic improvement over the first-order method [ADC(1)] and to a good agreement with experiment for photon energies below 80 eV. The use of extended second-order ADC theory [ADC(2)x] leads to a smaller further improvement. Above 80 eV photon energy all three methods lead to significant deviations from the experimental values which we attribute to the use of Gaussian single-electron bases. Our calculations show that the ADC(2)-Lanczos-Stieltjes technique is a reliable and efficient ab initio tool for theoretical prediction of total molecular photo-ionization cross-sections in the valence region.
Gesehen am 21.01.2022